2019
DOI: 10.3390/ma12193068
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultrasonic Nanocrystal Surface Modification on the Microstructure and Martensitic Transformation of Selective Laser Melted Nitinol

Abstract: Nitinol has significant potential for biomedical and actuating-sensing devices, thanks to its functional properties. The use of selective laser melting (SLM) with Nitinol powder can promote novel applications aimed to produce 3D complex parts with integrated functional performances. As the final step of the production route, finishing processing needs to be investigated both for the optimization of the surface morphology and the limit alteration of the Nitinol functional properties. In this work, the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 28 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…It is well reported that the richer Ti is, the more oxidation happens [22,27,43,44]. As reported in our previous works [28,[45][46][47][48] different SLM process parameters or post processing result in different compositions, microstructures, and thermomechanical behaviors of the as-fabricated NiTi alloys. Such a variation in composition and microstructure of as-fabricated alloys can differently affect the oxidation resistance.…”
Section: Microstructural Characterization Of Niti Scalementioning
confidence: 71%
“…It is well reported that the richer Ti is, the more oxidation happens [22,27,43,44]. As reported in our previous works [28,[45][46][47][48] different SLM process parameters or post processing result in different compositions, microstructures, and thermomechanical behaviors of the as-fabricated NiTi alloys. Such a variation in composition and microstructure of as-fabricated alloys can differently affect the oxidation resistance.…”
Section: Microstructural Characterization Of Niti Scalementioning
confidence: 71%
“…UNSM is a method that applies ultrasonic impacts to generate nanostructured surfaces. During UNSM, the ultrasonic waves are passed through a tungsten carbide tip at high frequencies (~20 kHz) and transposed onto a sample surface (see Figure 4 ) [ 129 ]. The UNSM is unique in that it can produce precise hierarchical surface patterns by accurately adjusting the operation parameters.…”
Section: Physical Surface Modification Of Biomedical Alloysmentioning
confidence: 99%
“…In the UNSM process, the primary function of the spherical roller tip is to create a mechanical impact and produce the SPD. In the case of USRP, the primary function of the spherical roller tip is to perform DR. Scholars adopted UNSM techniques on different steel grades [90][91][92][93][94], titanium alloys [95][96][97][98], aluminum alloys [99][100][101], and magnesium alloys [102,103], nickel alloys [89,104], copper alloys [105,106], shape memory alloys [107,108] high entropy alloys [109][110][111] and thus observed a significant enhancement in surface mechanical properties and surface integrity. In addition, there are advancements in USNM techniques, such as electropulsing-assisted UNSM and laser-assisted UNSM [112,113].…”
Section: Applications and Recent Advances Of Usrpmentioning
confidence: 99%